2022
DOI: 10.3389/fendo.2022.881309
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors in the Regulation of Leydig Cell Gene Expression and Function

Abstract: Cell differentiation and acquisition of specialized functions are inherent steps in events that lead to normal tissue development and function. These processes require accurate temporal, tissue, and cell-specific activation or repression of gene transcription. This is achieved by complex interactions between transcription factors that form a unique combinatorial code in each specialized cell type and in response to different physiological signals. Transcription factors typically act by binding to short, nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 122 publications
(166 reference statements)
1
22
0
Order By: Relevance
“…Testicular STAR expression and activity are acutely regulated by the gonadotropin LH (reviewed in [ 13 , 20 ]). LH stimulation also induces steroidogenesis in the testis, which triggers numerous signaling pathways, which in turn can activate several transcription factors including GATA4 (reviewed in [ 2 ]). We therefore hypothesized that acute Star regulation might be impaired in testes of p Star Δ19-GATAmut mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular STAR expression and activity are acutely regulated by the gonadotropin LH (reviewed in [ 13 , 20 ]). LH stimulation also induces steroidogenesis in the testis, which triggers numerous signaling pathways, which in turn can activate several transcription factors including GATA4 (reviewed in [ 2 ]). We therefore hypothesized that acute Star regulation might be impaired in testes of p Star Δ19-GATAmut mice.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of testicular steroidogenesis is complex and involves many regulatory molecules and mechanisms such as luteinizing hormone (LH), its signaling pathways, and the factors that interpret these signals [ 1 ]. The latter include most notably transcription factors acting on the expression of genes that encode steroidogenic enzymes and other proteins involved in the biosynthesis of testosterone (reviewed in [ 2 , 3 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GATA-4 protein de ciency effects the steroidogenesis metabolic pathways. The StAR gene includes a regulatory sequence recognized by GATA-4 proteins in the testes [15]. Studies have shown that steroidogenesis is affected by HIF1α protein and disruption of HIF1α protein signaling can relate to steroidogenesis disorders and reducing male reproductive function [5,36].…”
Section: Discussionmentioning
confidence: 99%
“…Testicular Leydig cells are located in the interstitial space of the seminiferous tubules in the testis. They are responsible for the synthesis and release of testosterone in mammals [15]. The steroidogenic acute regulatory (StAR) protein is involved in the transport of cholesterol from the outer mitochondrial membrane to the inner mitochondrial membrane and the enzyme CYP11A1 converts cholesterol to pregnenolone in the inner membrane of the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…FLCs are proposed to derive from progenitor cells originating within the adreno-gonadal primordium and other sources within the mesonephros, neural crest cells, coelomic epithelium [reviewed in ( 72 )]. Many transcription factors have been implicated in FLC differentiation and function [reviewed in ( 73 , 74 )]. GATA4 appears to play an integral role in both of these processes.…”
Section: Gata Factors In Fetal Testis Gene Expression and Functionmentioning
confidence: 99%